Penerapann Teori Progresivisme dalam Meningkatkan Mutu Pembelajaran Siswa SD Negeri Tegallega 1 Cipanas - Maman Suherman; Suharyanto H. Soro; Lastri Lestiawati; Ari Kukuh Kuntari (LP. Ma'arif Janggan Magetan, 2024)
Education is a dynamic process and as the main foundation in building a superior generation, and continues to develop, we as educators must be able to progress towards a better direction. Various educational theories have emerged to provide a philosophical and practical foundation in efforts to improve the quality of learning. One of the most influential theories is the theory of progressivism. This theory emphasizes active learning experiences, relevant to real life, and student-centered. This study aims to find out the extent to which the theory of progressivism has been applied in the learning process in elementary schools. The researchers used a qualitative research method. While the data collection method used observation and interview methods. The sample in this study were teachers and students. Research activities were carried out in 2024. The results of the study showed: (1) Increased student activity: students become more active in asking questions, discussing and solving problems, students do not only listen to what the teacher says. (2) Increased learning motivation: learning that is relevant to real life makes students more motivated and enthusiastic in participating in learning. (3) Development of critical thinking skills: through project-based activities and contextual learning, students are able to analyze, evaluate and solve independently and collaboratively. (4) Strengthening student character: students become more independent, responsible and able to work well together. (5) Learning materials are more relevant to students' daily lives so that they can more easily understand and apply knowledge in real situations. (6) Strengthening the relationship between teachers and students that emphasizes more dialogue between teachers and students can create a friendlier and more inclusive (comprehensive) environment. (7) Development of social skills, through group work and discussion, students can learn to communicate, cooperate and respect the opinions of their friends or the opinions of others.